Phlebotomus sergenti in a cutaneous leishmaniasis focus in Azilal province (High Atlas, Morocco): molecular detection and genotyping of Leishmania tropica, and feeding behavior. - Malika Ajaoud; Nargys Es-Sette; Rémi N Charrel; Abderahmane Laamrani-Idrissi; Haddou Nhammi; Myriam Riyad; Meryem Lemrani (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Phlebotomus (Paraphlebotomus) sergenti is at least one of the confirmed vectors for the transmission of cutaneous leishmaniasis caused by Leishmania tropica and distributed widely in Morocco. This form of leishmaniasis is considered largely as anthroponotic, although dogs were found infected with Leishmania tropica, suggestive of zoonosis in some rural areas. METHODOLOGY AND FINDINGS:This survey aimed at (i) studying the presence of Leishmania in field caught Phlebotomus sergenti, (ii) investigating genetic diversity within Leishmania tropica and (iii) identifying the host-blood feeding preferences of Phlebotomus sergenti. A total of 4,407 sand flies were collected in three rural areas of Azilal province, using CDC miniature light traps. Samples collected were found to consist of 13 species: Phlebotomus spp. and 3 Sergentomyia spp. The most abundant species was Phlebotomus sergenti, accounting for 45.75 % of the total. 965 female Phlebotomus sergenti were screened for the presence of Leishmania by ITS1-PCR-RFLP, giving a positive rate of 5.7% (55/965), all being identified as Leishmania tropica. Nucleotide heterogeneity of PCR-amplified ITS1-5.8S rRNA gene-ITS2 was noted. Analyses of 31 sequences obtained segregated them into 16 haplotypes, of which 7 contain superimposed peaks at certain nucleotide positions, suggestive of heterozygosity. Phlebotomus sergenti collected were found to feed on a large variety of vertebrate hosts, as determined by Cytochrome b sequencing of the DNA from the blood meals of 64 engorged females. CONCLUSION:Our findings supported the notion that Phlebotomus sergenti is the primary vector of Leishmania tropica in this focus, and that the latter is genetically very heterogeneous. Furthermore, our results might be suggestive of a certain level of heterozygosity in Leishmania tropica population. This finding, as well as the feeding of the vectors on different animals are of interest for further investigation.